2014
DOI: 10.1186/2050-5736-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sensory and cutaneous vascular responses to therapeutic ultrasound in the forearms of healthy volunteers

Abstract: BackgroundTherapeutic ultrasound (US) is used for a variety of clinical pathologies and is thought to accelerate tissue repair and help with pain reduction via its thermal and nonthermal effects. The evidence on physiological effects of US on both sensory and vascular functions in humans is incomplete. Hence, the purpose of this study was to determine the short-term impact of two doses of US (3 MHz, 1:4, 0.25 W/cm2, 5 min; 1 MHz, continuous, 0.8 W/cm2, 3 min), on sensory and vascular responses in the healthy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…Even though we were not able to present any objective difference either before or after treatment on the treated arm or between the treated or non-treated arms, patients expressed symptom deburdening in terms of a change in skin consistency, skin pain relief, and decreasing inflammation processes such as skin bursts. It is known that ultrasound increases cutaneous blood perfusion [27,28], and this may be the reason for the positive responses from the patients. Hence, a positive result of ultrasonic treatment in other forms of loose skin may not be applied in this symptom context.…”
Section: Discussionmentioning
confidence: 98%
“…Even though we were not able to present any objective difference either before or after treatment on the treated arm or between the treated or non-treated arms, patients expressed symptom deburdening in terms of a change in skin consistency, skin pain relief, and decreasing inflammation processes such as skin bursts. It is known that ultrasound increases cutaneous blood perfusion [27,28], and this may be the reason for the positive responses from the patients. Hence, a positive result of ultrasonic treatment in other forms of loose skin may not be applied in this symptom context.…”
Section: Discussionmentioning
confidence: 98%
“…In a study exploring muscle temperature, at 1MHz, 1.5 W/cm 2 and 2.0 W/cm 2 , the rate of temperature increase was so rapid that some of the participants were not able to complete the 10-minute treatment due to discomfort. 66 Shaik et al 54 used two treatment parameters on subjects: pulsed ultrasound at 3 MHz, 1:4 duty cycle, at an intensity of 0.25 W/cm 2 for 5 minutes and continuous ultrasound at 1 MHz, at an intensity of 0.8 W/cm 2 for 3 minutes. The results of this study found that there was a significant decrease in skin blood flow over the treatment area, comparing baseline to post-treatment measurements following both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study found that there was a significant decrease in skin blood flow over the treatment area, comparing baseline to post-treatment measurements following both treatments. 54 Skin blood flow was measured using a spectroscopy camera, examining the red blood cell concentration in dermal tissue. 54 Pulsed ultrasound at 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations